2008
DOI: 10.1289/ehp.11490
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, Lead, and Other Metals in Relation to Semen Quality: Human Evidence for Molybdenum as a Male Reproductive Toxicant

Abstract: BackgroundEvidence on human semen quality as it relates to exposure to various metals, both essential (e.g., zinc, copper) and nonessential (e.g., cadmium, lead), is inconsistent. Most studies to date used small sample sizes and were unable to account for important covariates.ObjectivesOur goal in this study was to assess relationships between exposure to multiple metals at environmental levels and human semen-quality parameters.MethodsWe measured semen quality and metals in blood (arsenic, Cd, chromium, Cu, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
156
7
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(184 citation statements)
references
References 34 publications
10
156
7
3
Order By: Relevance
“…Median total mercury in blood of 1.10 μg L -1 has not been associated with parameters of semen quality or endocrine function (109,123). An increased risk of subfertility was found to be associated with increasing levels of mercury in hair (124) ) in Swedish fi shermen did not affect sperm concentration, count, motility, chromatin integrity, or the proportion of Y-chromosome bearing sperm (125).…”
Section: Effects Of Environmental Exposure To Metals On Reproductive mentioning
confidence: 86%
See 3 more Smart Citations
“…Median total mercury in blood of 1.10 μg L -1 has not been associated with parameters of semen quality or endocrine function (109,123). An increased risk of subfertility was found to be associated with increasing levels of mercury in hair (124) ) in Swedish fi shermen did not affect sperm concentration, count, motility, chromatin integrity, or the proportion of Y-chromosome bearing sperm (125).…”
Section: Effects Of Environmental Exposure To Metals On Reproductive mentioning
confidence: 86%
“…Moreover, blood lead level <150 µg L -1 has been associated with higher serum levels of testosterone and oestradiol, and lower serum levels of prolactin (66). In men with median blood lead of 15 µg L -1 , an inverse association with serum prolactin and thyroid stimulating hormone (107) was found, but there was no association between blood lead levels and sperm concentration, motility or morphology (109). A Mexican study in men showed a signifi cant association between lower semen quality and lead in spermatozoa or seminal fl uid, but not with blood lead (106).…”
Section: Effects Of Environmental Exposure To Metals On Reproductive mentioning
confidence: 99%
See 2 more Smart Citations
“…An elevated level of molybdenum in r uminants causes a disease known as hypercuprosis (Ward 1978). Recent data showed that molybdenum is toxic to spermatogenesis and embryogenesis in animals, including catfish and mice (Meeker et al 2008;Bi et al 2013;Zhai et al 2013;Zhang et al 2013). Toxic effect of molybdenum to these animals warrants removal of molybdenum from the environment.…”
Section: Introductionmentioning
confidence: 99%